2015
DOI: 10.1111/dom.12436
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness and safety of vildagliptin in >19 000 patients with type 2 diabetes: the GUARD study

Abstract: The present GUARD study was a prospective, non-interventional study evaluating the clinical effectiveness, safety and tolerability of vildagliptin with or without metformin in adult patients with type 2 diabetes mellitus (T2DM) studied in routine clinical practice. Patients were enrolled from countries across four geographical regions. The primary endpoint was change in glycated haemoglobin (HbA1c) concentration from baseline after 24 weeks of treatment with vildagliptin with or without metformin. Of 19 331 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
2
7
0
1
Order By: Relevance
“…Furthermore, there were no clear differences in the efficacy of vildagliptin when stratified by age or BMI, which supports previous observations that no dose adjustment is required according to these patient characteristics [19]. The efficacy of vildagliptin in combination with Met, in terms of reduction in HbA1c, was comparable with observational trials such as GUARD [12] and GALATA [20], although differences in the background of patients and the study designs preclude direct comparisons.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, there were no clear differences in the efficacy of vildagliptin when stratified by age or BMI, which supports previous observations that no dose adjustment is required according to these patient characteristics [19]. The efficacy of vildagliptin in combination with Met, in terms of reduction in HbA1c, was comparable with observational trials such as GUARD [12] and GALATA [20], although differences in the background of patients and the study designs preclude direct comparisons.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, there were no differences observed in the incidence rates of gastrointestinal AEs such as anorexia, nausea, vomiting, diarrhea, dyspepsia, constipation, abdominal pain, or feeling bloated. The GUARD study [12] showed that vildagliptin therapy over 24 weeks was well tolerated, regardless of concomitant Met administration. Similarly, a small Japanese trial that investigated the uptitration of Met in patients receiving vildagliptin therapy found no tolerability issues with patients receiving up to 1000 mg/day Met [13], which also confirmed the findings of a previous study conducted in Japan [14].…”
Section: Discussionmentioning
confidence: 99%
“…Because T2DM is characterized by continuing deterioration of pancreatic islet -cell function over time, it is possible that in obese patients with shorter T2DM duration, HbA1c level could still be adequately controlled with metformin. Although previous studies all reported that VLDM's efficacy is independent of patients' baseline age, BMI and disease duration [20,22,23,[34][35][36], it is still possible that a combination of these factors could have contributed to the lack of VLDM superiority for this subgroup of patients. Nevertheless, the present results suggest that an individualized treatment regimen for different patients is possible and such individualized treatment could facilitate better treatment efficacy; for example, for overweight/obese younger patients with T2DM who can tolerate the GI AEs associated with metformin, VLDM and HDM are equally feasible choices, but for other patients, VLDM might be preferable.…”
Section: Discussionmentioning
confidence: 89%
“…In a post hoc subgroup analysis based on patients' age (<65 or ≥65 years) or BMI (<30 or ≥30 kg/m 2 ), conducted in a study that evaluated efficacy of vildagliptin add‐on therapy, efficacy of vildagliptin add‐on therapy was shown regardless of age or BMI status, although patients aged <65 years, and BMI <30 kg/m 2 had slightly better HbA1c reduction . In other studies, age (<65 or ≥65 years) or BMI (<30 or ≥30 kg/m 2 ) was not associated with the effectiveness of vildagliptin and metformin combination therapy . These results seemed to suggest that BMI did not affect the treatment efficacy of some antidiabetic medications, at least not independently.…”
Section: Introductionmentioning
confidence: 98%
“…Снижение уровня HbA 1c имело место на всех стадиях СД2 (рис. 7) независимо от пола, возраста и степени ожирения пациентов [60].…”
Section: вилдаглиптин в реальной клинической практике (ркп)unclassified